Propuesta de mejora en la gestión logística para reducir los costos operativos de la empresa Construcciones WBA E.I.R.L en la ciudad de Chepén - Hoyos Llanos, Silver Tony (2017)
This research work entitled "PROPOSAL OF IMPROVEMENT IN LOGISTICS MANAGEMENT TO REDUCE THE OPERATING COSTS OF THE COMPANY CONSTRUCCIONES WBA E.I.R.L. IN THE CITY OF CHEPEN "; Its general objective is: Propose an improvement plan for logistics management that allows reducing the operating costs of the company Construcciones Wba EIRL in the city of Chepen. For the present research report, the descriptive design was used, as well as the methods: deductive-inductive, analytical, synthetic and statistical method. In the techniques of data collection, the survey was used. According to the results obtained, we have the main shortcoming in the logistics process is the delay in the acquisition of materials, the main cause of the failure is the availability of cash, 40% of employees indicate that they almost never plan in the acquisitions of goods and services, 95% of employees have never received training in logistics management, 35% of employees never perform well the requirements, the main weakness found in the requirements is the lack of technical specifications of materials , the operating costs incurred are the costs for the return of materials, labor, general expenses and penalties, it is lost due to operating costs represents 4.88% of the total turnover of the company, 65% of the suppliers They have a rating of bad and very bad.